Three wild dogs (and the truth) : a memoir - Zusak, Markus (Harper, an imprint of HarperCollins Publishers, 2024)
"What happens when the Zusak family opens their home to three big, wild, street-hardened dogs--Reuben, more wolf than hound; Archer, blond, beautiful, destructive; and the rancorously smiling Frosty, who walks like a rolling thunderstorm? The answer can only be chaos: there are street fights, park fights, public shamings, property damages, injuries, hospital visits, wellness checks, pure comedy, shocking tragedy, and carnage that must be read to be believed. ... [This is a] memoir about the human need for both connection and disorder, a love letter to the animals who bring hilarity and beauty--but also the visceral truth of the natural world--straight to our doors and into our lives and change us forever"--